RELEVANSI USHUL FIQH SEBAGAI METODOLOGI PENETAPAN HUKUM EKONOMI ISLAM DALAM MENJAWAB TANTANGAN EKONOMI MODERN - Ahmad Ali Kamal; Moh. Bahrudin; Syamsul Hilal (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
Usul Fiqh is a methodological foundation for establishing Islamic law, functioning not only in the realm of worship but also has significant relevance in the modern economy. In the context of the development of the global economic system, various contemporary issues have emerged, such as Islamic banking, insurance, investment, and Islamic financial instruments, which require legal clarity in accordance with Sharia principles. This article aims to analyze the position of Usul Fiqh as a methodology for establishing Islamic economic law and how its principles can address the challenges of the modern economy. The approach used is qualitative with descriptive comparative analysis, examining the views of the four major schools of thought Hanafi, Maliki, Shafi'i, and Hanbali in linking the principles of Usul Fiqh to contemporary economic practices. The research findings demonstrate that Usul Fiqh plays a crucial role in establishing a legal foundation for Islamic economics that is adaptive to changing times, while maintaining the integrity of sharia through the principles of maslahah, istihsan, and qiyas. Each school of thought (mazhab) has its own methodological contributions in interpreting the evolving economic context, which collectively enriches the treasury of Islamic economic law. Therefore, Usul Fiqh can be viewed as a dynamic methodology capable of bridging normative texts and modern economic realities